The efficacy of Equine Assisted Therapy intervention in gross motor function, performance, and spasticity in children with Cerebral Palsy - Stergiou, Alexandra N.; Mattila-Rautiainen, Sanna; Varvarousis, Dimitrios N.; Tzoufi, Meropi; Plyta, Panagiota; Beris, Alexandros; Ploumis, Avraam (Frontiers in Veterinary Science, 2023)
Purpose To evaluate the efficacy of Equine Assisted Therapy in children with Cerebral Palsy, in terms of gross motor function, performance, and spasticity as well as whether this improvement can be maintained for 2 months after the end of the intervention. Methods Children with Cerebral Palsy participated in this prospective cohort study. The study lasted for 28 weeks, of which the equine assisted therapy lasted 12 weeks taking place once a week for 30 min. Repeated measures within the subject design were used for the evaluation of each child’s physical performance and mental capacity consisting of six measurements: Gross Motor Function Measure-88 (GMFM-88), Gross Motor Performance Measure (GMPM), Gross Motor Function Classification System (GMFCS), Modified Ashworth Scale (MAS) and Wechsler Intelligence Scale for Children (WISC III). Results Statistically significant improvements were achieved for 31 children in Gross Motor Function Measure and all its subcategories (p < 0.005), also in total Gross Motor Performance Measure and all subcategories (p < 0.005). These Gross Motor Function Measure results remained consistent for 2 months after the last session of the intervention. Regarding spasticity, although an improving trend was seen, this was not found to be statistically significant. Conclusion and implications Equine Assisted Therapy improves motor ability (qualitatively and quantitatively) in children with Cerebral Palsy, with clinical significance in gross motor function.